Review of the Effectiveness of Roof-Mounted Solar Panels Compared to Wall-Mounted Residential Houses in South Sumatra Island Indonesia - Muhammad Rayyan Harahap; Suryadhi Firdaus; Rusdianasari Rusdianasari (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2025)
Solar energy, one of the most abundant and widely used renewable resources in the world, delivers an incredible amount of power. In just one hour, the amount of solar energy striking the Earth's surface is approximately 410-430 trillion joules, which exceeds the total energy consumption of all humans, estimated at around 400-410 trillion joules. This energy is widely utilized for household purposes. According to data from the Ministry of Energy and Mineral Resources, R-3 customers”those using electricity above 6,600 VA”have an average national consumption of 122 kWh per month. This electricity demand is still primarily supplied by PLN (State Electricity Company). Household electricity supply from PLN can be supplemented with solar power generated by solar panels. To optimize the use of available space, solar panels can be installed on rooftops or exterior walls of houses. In this journal, the author will review the effectiveness of solar panels installed on rooftops which called as Roof Mounted Solar Panel and exterior walls of residential houses or so called as Wall Mounted. The review focuses on the power production of solar panels placed in these different locations at the same coordinates simultaneously. The research is conducted using the Experimental Research Method.